1978
DOI: 10.1288/00005537-197810000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Laser surgery and immunotherapy in the management of laryngeal papilloma

Abstract: Twenty-three cases of laryngeal papilloma have been treated and followed for four years utilizing laser excision and laser excision/immunotherapy. Fourteen cases responded well to laser excision alone, nine did not and immunotherapy was instituted as adjunctive treatment. To date, immunotherapy has contributed little to the relief in this group of refractory cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…When put together, these three databases revealed 1202 cases of RRP with 28 cases of lung involvement; the calculated incidence of 2.3% is quite similar to that derived from the cohort studies, and higher than the previously reported incidence of less than 1% [6,7] This latter estimate comes from a review of eight publications from the 1950s to 1970s, with a total of 532 cases of RRP. Our review of these publications [103,[120][121][122][123][124][125][126] reveals that lung involvement was not often sought and some of the publications had cases of adultonset RRP. This might explain the low reported incidence.…”
Section: Lung Involvement In Rrp--the Cohort Studiesmentioning
confidence: 99%
“…When put together, these three databases revealed 1202 cases of RRP with 28 cases of lung involvement; the calculated incidence of 2.3% is quite similar to that derived from the cohort studies, and higher than the previously reported incidence of less than 1% [6,7] This latter estimate comes from a review of eight publications from the 1950s to 1970s, with a total of 532 cases of RRP. Our review of these publications [103,[120][121][122][123][124][125][126] reveals that lung involvement was not often sought and some of the publications had cases of adultonset RRP. This might explain the low reported incidence.…”
Section: Lung Involvement In Rrp--the Cohort Studiesmentioning
confidence: 99%
“…More recently, interest has turned to adjuvant immunotherapy (Lyons et al, 1978), and later Interferon synthesis, in an attempt to induce virus remission by invoking natural immune defences. Early experience with crude interferon was asssociated with malaise and fever, and occasionally marrow depression in the recipients (Merigan, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Interferon has been used in conjunction with Laser therapy and, although the immediate effects are beneficial, to date there have been few reports of significant increase in the remission time (Bomholt, 1983), and the longterm effects of Interferon are as yet not fully known (Haglund et al, 1981;Lyons et al, 1978). Various chemical treatments have also been described, including chemotherapy (Smith et al, 1980), with unproven efficacy or side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…In 1976, Strong et al45 reported 110 cases treated by this method; one third achieved remissions that lasted 1 or more years. In 1978, Lyons et al 25 also reported satisfactory responses in 14 of 23 cases. In their opinion, firm papillomas responded well to simple laser excision, unlike the soft, grapelike cluster papillomas, which showed the highest recurrence.…”
Section: Surgical Measuresmentioning
confidence: 95%